A topography of dots: new perspectives on the history and legend of the Forty Thieves - Shaw, Kim (Crime, histoire & sociétés, 2022)
Accounts of criminal organisations referred to as the "Forty Thieves" have been noted throughout nineteenth century Britain. While the profile of alleged members takes several different forms, the most common descriptions refer to gangs of youth who commit acts of coordinated theft in public spaces and at community events. Included in these accounts are repeated references to tattooed markings said to identify gang members. These consisted of a series of dots ranging from five to nine in number and were often concealed between the thumb and forefinger. While these accounts sparked the imagination of the British public and continue to contribute to what might be called the legend of the Forty Thieves, work to validate the truth of their specific claims has, to date, been limited. This study addresses this gap through an analysis of the recorded physical descriptions of over 40,000 convicts transported to Van Diemen’s Land between the years 1816-1853. Focusing on the presentation of dot pattern tattoos, it was found that convicts marked with five and seven dots differ from other convicts in two significant ways. Firstly, they are more likely to have a record of previous convictions; and secondly, they are considerably younger in age. We also recorded distinct regional differences in the acquisition of dot patterns for subjects born in different parts of Britain. While these findings support the assertion that such markings may in fact be indicative of juvenile criminal gangs, we conclude that the ubiquity of these markings and their geographic spread, both across Britain and beyond, implies that the Forty Thieves never existed as a discrete criminal organisation.